Looking for Redemption in a Globalized North: Representations of the Arctic in Judith Hermann’s Short Stories Kaltblau (Cold-Blue) and Die Liebe zu Ari Oskarsson (Love for Ari Oskarsson) - Gremler, Claudia (Nordlit, 2008)
This paper explores the literary representation of Iceland and Norway in two short stories by contemporary German writer Judith Hermann. It analyses both the depiction of these countries as part of the globalised western world and the redemptive power they are tentatively ascribed by the author. Continuing a long German tradition of looking at Scandinavia from an almost colonial perspective, Hermann on the one hand presents these northern countries as a mere extension of central Europe, largely devoid of distinguishing national characteristics. At the same time she makes reference to the topos of the north as a vast and empty space and highlights both the specific arctic nature of the environment and the effect it has on her urban characters, who find themselves on a search for meaning and orientation in a postmodern fragmented world. Despite Hermann's overall sceptical attitude towards her characters' quest for happiness, these northern locations ultimately appear as potential places of self-realisation and enlightenment.